STRATEGI PEMASARAN MELALUI SOCIAL MEDIA INSTAGRAM DAN TIKTOK UNTUK MENINGKATKAN PENJUALAN - Amalia, Lahmirza Aula; Zulistiani, Zulistiani; Damayanti, Susi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
Instagram and TikTok's social networking platforms have attracted a significant number of new users from the global community, which Ardana Studio has leveraged to grow its design business. The researcher's objective is to analyze marketing tactics on social media in order to boost sales at Ardana Studio. This research employs a qualitative approach, using case studies. The researcher assumes the role of a key informant. Data collection methods include observation, interviews, and documentation. The data is analyzed using reduction techniques, and the findings are presented and verified with the owner of Ardana Studio. The validity of the research is ensured through data triangulation and various techniques. The findings reveal that Ardana Studio has expanded its market segmentation as a creative design business by creating comprehensive business profiles that are widely reviewed by users on Instagram and TikTok. The marketing strategy focuses on content pillars, content calendars, and content creation concepts. By implementing a marketing strategy through Instagram and TikTok, which introduces engaging information in their profiles, Ardana Studio has successfully increased design sales and attracted foreign consumers.